Low-cobalt positive electrode active material, preparation method thereof, electrochemical device and electronic device

By regulating the XRD spectrum characteristic parameters of low-cobalt ternary materials and adding titanium and aluminum sources to the sintering treatment, a low-cobalt positive electrode active material with optimal crystallinity and fluidity is formed, solving the challenges of low-cobalt ternary materials in terms of capacity and cyclic performance and achieving efficient electrochemical performance.

CN114759183BActive Publication Date: 2025-03-18ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210602204.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-30
Publication Date
2025-03-18
Estimated Expiration
2042-05-30

AI Technical Summary

Technical Problem

Existing low-cobalt ternary materials have challenges in improving capacity and cycling performance, especially the reduction in nickel content leads to a decrease in energy density, which affects conductivity and lithium ion diffusion.

Method used

By selecting a specific coating material and controlling the characteristic parameters in the XRD spectrum of the low-cobalt positive electrode active material, a material with optimal crystallinity and fluidity is formed. The specific method includes adding a titanium source and an aluminum source on the basis of the low-cobalt ternary material precursor and lithium salt, and sintering treatment to form a core and a cladding layer, and jointly improving the overall crystallinity of the material.

Benefits of technology

The charge and discharge capacity, Coulomb efficiency and cycle capacity retention rate of the electrochemical device are improved, and the efficient performance of low-cobalt ternary materials is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114759183B_ABST
    Figure CN114759183B_ABST
Patent Text Reader

Abstract

The present invention provides a low-cobalt positive electrode active material, a preparation method thereof, an electrochemical device and an electronic device, wherein the low-cobalt positive electrode active material comprises a low-cobalt positive electrode active material core and a coating layer coated on the surface thereof, wherein the low-cobalt positive electrode active material core comprises titanium and aluminum elements, and the coating layer comprises titanium compounds and aluminum compounds; the XRD spectrum of the low-cobalt positive electrode active material satisfies: the position of the (003) crystal plane diffraction peak is 18.40° to 18.60°, the half-height width of the diffraction peak is 0.140° to 0.160°, the grain size is 44.28° to 44.32°, and the half-height width of the diffraction peak is 0.150° to 0.190°. The low-cobalt positive electrode active material of the present invention has good crystallinity and fluidity, and the electrochemical device prepared by using the low-cobalt positive electrode active material has high charge and discharge gram capacity, coulomb efficiency and cycle capacity retention rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a low-cobalt positive electrode active material, a preparation method thereof, an electrochemical device and an electronic device. Background Art

[0002] Ternary layered material LiNi x Co y Mn 1-x-y O 2 It has a high theoretical specific capacity and reaction platform voltage, and excellent kinetic performance. It has been widely used in high energy density power battery systems. In the prior art, ternary materials often use a lower nickel content to maintain their own good safety performance; at the same time, the cost of cobalt in ternary materials is high, and the content of cobalt in nature is gradually decreasing. Therefore, low-cobalt ternary materials have gradually emerged, making up for the shortcomings of traditional ternary materials with slightly poor safety performance and high cost.

[0003] In ternary materials, the nickel content plays a vital role in the overall capacity of the material. Reducing the nickel content will lead to a decrease in the energy density of the material, while the cobalt content will affect the overall conductivity of the material. Reducing the cobalt content will increase the diffusion barrier of lithium ions in the lattice, thereby affecting the reaction kinetics of the material. Therefore, improving the capacity and cycle performance of low-cobalt ternary materials has important research significance. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a low-cobalt positive electrode active material, a preparation method thereof, an electrochemical device and an electronic device. The present invention selects a specific coating material and adjusts the characteristic parameters in the XRD spectrum of the low-cobalt positive electrode active material to obtain a low-cobalt positive electrode active material with the best crystallinity and fluidity, thereby improving the charge and discharge gram capacity, coulomb efficiency and cycle capacity retention rate of the prepared electrochemical device.

[0005] In the present invention, "low cobalt" means that the amount of cobalt in the nickel-cobalt-manganese ternary material does not exceed 13% of the total amount of nickel-cobalt-manganese.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a low-cobalt positive electrode active material, the low-cobalt positive electrode active material comprising a low-cobalt positive electrode active material core and a coating layer coated on the surface of the low-cobalt positive electrode active material core, the low-cobalt positive electrode active material core comprising titanium and aluminum elements, the coating layer comprising a titanium compound and an aluminum compound, and the XRD spectrum of the low-cobalt positive electrode active material satisfies:

[0008] The position of the (003) crystal plane diffraction peak in the XRD spectrum is 18.40° to 18.60°, the half-height width of the (003) crystal plane diffraction peak is 0.140° to 0.160°, and the grain size of the (003) crystal plane is to The position of the (104) crystal plane diffraction peak is 44.28° to 44.32°, and the half-height width of the (104) crystal plane diffraction peak is 0.150° to 0.190°.

[0009] In the present invention, the position of the (003) crystal plane diffraction peak in the XRD spectrum of the low-cobalt positive electrode active material is 18.40° to 18.60°, for example, it can be 18.40°, 18.42°, 18.44°, 18.46°, 18.48°, 18.50°, 18.52°, 18.54°, 18.56°, 18.58° or 18.60°, etc.; the half-height width of the (003) crystal plane diffraction peak is 0.140° to 0.160°, for example, it can be 0.140°, 0.142°, 0.144°, 0.146°, 0.148°, 0.150°, 0.152°, 0.154°, 0.156°, 0.158° or 0.160°, etc.; the grain size of the (003) crystal plane is to For example it could be or etc., the grain size of the (003) crystal plane refers to the grain size obtained by fitting the corresponding peak of the (003) crystal plane; the position of the diffraction peak of the (104) crystal plane is 44.28° to 44.32°, for example, it can be 44.28°, 44.29°, 44.30°, 44.31° or 44.32°, etc.; the half-height width of the diffraction peak of the (104) crystal plane is 0.150° to 0.190°, for example, it can be 0.150°, 0.155°, 0.160°, 0.165°, 0.170°, 0.175°, 0.180°, 0.185° or 0.190°, etc.

[0010] The low-cobalt positive electrode active material of the present invention comprises a low-cobalt positive electrode active material core and a coating layer coated on the surface thereof, the low-cobalt positive electrode active material core is doped with titanium and aluminum, and the titanium and aluminum are located in the transition metal layer of the core or in the grain boundary; the coating layer in the low-cobalt positive electrode active material contains titanium compounds and aluminum compounds, and the titanium and aluminum in the core and the coating layer act synergistically, which helps the rock salt phase near the surface to transform into a layered structure during the material preparation process, thereby improving the overall crystallinity of the material. At the same time, the low-cobalt positive electrode active material of the present invention has suitable XRD spectrum characteristic parameters, namely the diffraction peak position, half-height width and grain size of the (003) and (104) crystal planes, and the above parameters are all controlled in the most suitable range, so that a material with the best crystallinity and fluidity can be obtained, thereby showing a higher gram capacity and excellent cycle capacity retention rate in the battery.

[0011] Preferably, the stacking angle of the low-cobalt positive electrode active material is 45° to 55°, for example, it can be 45°, 46°, 47°, 48°, 49°, 50°, 51°, 52°, 53°, 54° or 55°.

[0012] In the present invention, by further limiting the stacking angle of the low-cobalt positive electrode active material and combining it with specific XRD spectrum characteristic parameters, the crystallinity and fluidity of the material are improved, thereby improving the gram capacity and cycle capacity retention rate of the material.

[0013] It should be noted that the half-height width of the diffraction peak in the XRD spectrum, the grain size and the stacking angle of the low-cobalt positive electrode active material are all well-known in the art. The half-height width (FWHM), also known as the half-peak width, represents the peak width when the peak height is half. The grain size can be calculated by the Scherrer formula d = 0.89*γ / (B*cosθ), where γ is the X-ray wavelength, and γ in this application is B is the half-height width of the (003) crystal plane, and θ is the diffraction angle of the (003) crystal plane. The stacking angle is the powder stacking angle, also known as the angle of repose or the angle of repose, which refers to the maximum angle between the surface of the bulk material pile naturally formed on the plane and the horizontal plane.

[0014] Preferably, along the surface of the low-cobalt positive electrode active material inward, the distribution depth of the aluminum element in the inner core of the low-cobalt positive electrode active material is higher than the distribution depth of the titanium element.

[0015] In a second aspect, the present invention provides a method for preparing the low-cobalt positive electrode active material according to the first aspect, the preparation method comprising the following steps:

[0016] (1) mixing a low-cobalt ternary material precursor and a lithium salt, and sintering once at 935° C. to 955° C. to obtain a first sintered product;

[0017] (2) mixing the first sintered product, a titanium source and an aluminum source, and performing secondary sintering to obtain the low-cobalt positive electrode active material;

[0018] Among them, based on the total mass of metal elements in the low-cobalt ternary material precursor, lithium salt, titanium source and aluminum source, the content of titanium element in the titanium source is 400ppm to 1200ppm, and the content of aluminum element in the aluminum source is 500ppm to 1500ppm.

[0019] In the present invention, the primary sintering temperature is 935°C to 955°C, for example, it can be 935°C, 938°C, 940°C, 942°C, 945°C, 948°C, 950°C, 952°C or 955°C, etc.; based on the total mass of the metal elements in the low-cobalt ternary material precursor, lithium salt, titanium source and aluminum source, the content of titanium element in the titanium source is 400ppm to 1200ppm, for example, it can be 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm or 1200ppm, etc.; the content of aluminum element in the aluminum source is 500ppm to 1500ppm, for example, it can be 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm or 1500ppm, etc.

[0020] In the present invention, a low-cobalt ternary material precursor and a lithium salt are first sintered at a temperature of 935° C. to 955° C., the crystal plane parameters and grain parameters of the material are adjusted, and then a first sintered product with a better crystal structure obtained by the first sintering is mixed with a titanium source and an aluminum source with a specific content and sintered to form an amorphous structure of Li-Al-O and Li-Ti-O on the surface of the inner core. The synergistic effect of the titanium source and the aluminum source helps to transform the rock salt-like phase near the surface of the material into a layered structure, improves the overall crystallinity of the material, and obtains a low-cobalt positive electrode active material with the best crystallinity and fluidity, thereby improving the charge and discharge gram capacity, coulomb efficiency and cycle capacity retention rate of the prepared electrochemical device.

[0021] Preferably, the primary sintering time is 15 h to 21 h, for example, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h or 21 h.

[0022] As a preferred technical solution of the preparation method of the present invention, the temperature of the secondary sintering is 400°C to 700°C, for example, it can be 400°C, 450°C, 500°C, 520°C, 550°C, 580°C, 600°C, 620°C, 650°C, 680°C or 700°C, and is further preferably 450°C to 700°C. A titanium source and an aluminum source are added at a suitable temperature for coating, and the crystal plane parameters and grain parameters of the material are further optimized in combination with the first sintering product with a better crystal structure to obtain a material with optimal crystallinity and fluidity.

[0023] Preferably, the secondary sintering time is 5 h to 15 h, for example, 5 h, 8 h, 10 h, 12 h or 15 h.

[0024] Preferably, the gas in the atmosphere of the primary sintering and the secondary sintering includes oxygen, and the volume of oxygen in the atmosphere accounts for greater than or equal to 80% of the total volume of the gas, for example, it may be 80%, 82%, 84%, 96%, 88%, 90%, 92%, 94%, 96%, 98% or 100%, etc.

[0025] Preferably, the molar ratio of the low-cobalt ternary material precursor to the lithium salt is 1:(0.95 to 1.05), for example, it can be 1:0.95, 1:0.98, 1:1, 1:1.02 or 1:1.05, etc.

[0026] Preferably, the chemical formula of the ternary material precursor is Ni x Co y Mn 1-x-y (OH) 2 , wherein 0.56≤x≤0.60, for example, it can be 0.56, 0.57, 0.58, 0.59 or 0.6, etc., 0.09≤y≤0.13, for example, it can be 0.09, 0.1, 0.11, 0.12 or 0.13, etc. The low-cobalt ternary material precursor within this element ratio range can not only improve the safety of the finished battery, but also reduce the use of the rare element Co.

[0027] Preferably, the lithium salt comprises lithium carbonate and / or lithium hydroxide.

[0028] Preferably, the titanium source comprises titanium oxide.

[0029] Preferably, the aluminum source comprises aluminum oxide.

[0030] In a third aspect, the present invention provides an electrochemical device, wherein a positive electrode of the electrochemical device comprises the low-cobalt positive electrode active material according to the first aspect.

[0031] The electrochemical device provided by the invention has higher charge and discharge gram capacity, higher coulomb efficiency and better cycle stability.

[0032] In an optional embodiment, the present invention provides a method for detecting whether an electrochemical device contains the low-cobalt positive electrode active material of the present invention, comprising:

[0033] The electrochemical device sample is split to obtain a positive electrode, the positive electrode is rinsed with a solvent and dried, and the surface of the positive electrode is scraped to obtain an active material powder, and the active material powder is tested by XRD and focused ion beam scanning electron microscopy (FIB-SEM) to observe the position, half-height width and grain size of the diffraction peaks of the (003) crystal plane and the (104) crystal plane in the XRD spectrum, as well as the FIB-SEM test results;

[0034] If the XRD test shows that the position of the (003) crystal plane diffraction peak is 18.40° to 18.60°, the half-height width is 0.140° to 0.160°, and the grain size is to The position of the (104) crystal plane diffraction peak is 44.28° to 44.32°, the half-height width is 0.150° to 0.190°, and the FIB-SEM test shows that the active powder contains lithium, nickel, cobalt, manganese, titanium and aluminum elements, which confirms that the positive electrode of the electrochemical device sample contains the low-cobalt positive electrode active material described in the present invention.

[0035] Furthermore, if the stacking angle of the active material powder is 45° to 55°, and / or the penetration depth of the aluminum element in the active material powder is higher than the penetration depth of the titanium element, it can be further confirmed that the positive electrode of the electrochemical device sample contains the low-cobalt positive electrode active material described in the present invention.

[0036] In an optional embodiment, the present invention provides a method for preparing the positive electrode, comprising:

[0037] The low-cobalt positive electrode active material, the conductive agent and the binder are mixed with a solvent to obtain a positive electrode slurry, and the positive electrode slurry is coated on an aluminum foil and rolled to obtain a positive electrode.

[0038] Preferably, the conductive agent includes conductive carbon black (SP) and / or carbon nanotubes (CNT).

[0039] Preferably, the binder comprises polyvinylidene fluoride (PVDF).

[0040] Preferably, the mass ratio of the low-cobalt positive electrode active material, SP, CNT and PVDF is (90 to 99):1:0.5:1, for example, it can be 90:1:0.5:1, 92:1:0.5:1, 94:1:0.5:1, 96:1:0.5:1, 98:1:0.5:1 or 99:1:0.5:1, etc.

[0041] In an alternative embodiment, the electrochemical device is a lithium ion battery.

[0042] In an optional embodiment, the negative electrode of the electrochemical device includes graphite, SP, carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), and the mass ratio of graphite, SP, CMC and SBR is (90 to 99):1:1.5:2, for example, it can be 90:1:1.5:2, 92:1:1.5:2, 94:1:1.5:2, 96:1:1.5:2, 98:1:1.5:2 or 99:1:1.5:2, etc.

[0043] In an optional embodiment, the electrolyte of the electrochemical device includes a lithium salt and a solvent.

[0044] In an alternative embodiment, the lithium salt comprises LiPF 6 .

[0045] In an optional embodiment, based on 100wt% of the mass of the electrolyte, the content of the lithium salt is 4wt% to 24wt%, for example, 4wt%, 8wt%, 10wt%, 15wt%, 20wt% or 24wt%.

[0046] In an optional embodiment, the solvent includes at least one of ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) and polycarbonate (PC), or a combination of any two thereof, for example, a combination of EC and EMC, a combination of DMC and PC, a combination of EC, EMC and DMC, or a combination of EC, EMC, DMC and PC, etc.

[0047] In an optional embodiment, the mass ratio of EC, EMC, DMC and PC in the solvent is (2 to 4): (3 to 5): (2 to 4): (0 to 1), the selection range of EC (2 to 4) can be, for example, 2, 2.5, 3, 3.5 or 4, the selection range of EMC (3 to 5) can be, for example, 3, 3.5, 4, 4.5 or 5, the selection range of DMC (2 to 4) can be, for example, 2, 2.5, 3, 3.5 or 4, the selection range of PC (0 to 1) can be, for example, 0, 0.1, 0.2, 0.3, 0.5, 0.7 or 1, etc. When PC is 0, it means that the solvent does not contain PC.

[0048] In an optional embodiment, the thickness of the separator of the electrochemical device is 9 μm to 18 μm, for example, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm or 18 μm.

[0049] In an optional embodiment, the permeability of the diaphragm of the electrochemical device is 180s / 100mL to 380s / 100mL, for example, it can be 180s / 100mL, 200s / 100mL, 240s / 100mL, 250s / 100mL, 280s / 100mL, 300s / 100mL, 250s / 100mL or 380s / 100mL, etc.

[0050] In an optional embodiment, the porosity of the diaphragm of the electrochemical device is 30% to 50%, for example, it may be 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48% or 50%, etc.

[0051] The present application selects a diaphragm with suitable parameters to cooperate with a positive electrode and a negative electrode to prepare an electrochemical device, thereby improving the capacity and cycle stability of the electrochemical device.

[0052] In a fourth aspect, the present invention provides an electronic device, wherein the electronic device comprises the electrochemical device according to the third aspect.

[0053] Exemplarily, the electronic device of the present invention may be a mobile computer, a portable phone, a memory card, a liquid crystal television, a car, a motorcycle, a motor, a clock, a camera, etc.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] The low-cobalt positive electrode active material of the present invention comprises a low-cobalt positive electrode active material core and a coating layer coated on the surface thereof, the low-cobalt positive electrode active material core is doped with titanium and aluminum elements, the coating layer contains titanium compounds and aluminum compounds, the titanium and aluminum in the core and the coating layer act synergistically, which helps the rock salt-like phase near the surface to transform into a layered structure during the material preparation process, thereby improving the overall crystallinity of the material. At the same time, the low-cobalt positive electrode active material of the present invention has suitable XRD spectrum characteristic parameters, namely the diffraction peak position, half-height width and grain size of the (003) and (104) crystal planes, and the above parameters are all controlled in the most suitable range, so that a material with the best crystallinity and fluidity can be obtained, thereby showing a higher gram capacity and excellent cycle capacity retention rate in the battery. DETAILED DESCRIPTION

[0056] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0057] Example 1

[0058] This embodiment provides a low-cobalt positive electrode active material, including a low-cobalt positive electrode active material core and a coating layer coated on the surface of the low-cobalt positive electrode active material core, the low-cobalt positive electrode active material core is doped with titanium and aluminum elements, the coating layer includes amorphous Li-Al-O and Li-Ti-O, and the stacking angle of the low-cobalt positive electrode active material is 50°.

[0059] The XRD spectrum of the low-cobalt positive electrode active material satisfies:

[0060] The position of the (003) crystal plane diffraction peak in the XRD spectrum is 18.578°, the half-maximum width (FWHM) of the (003) crystal plane diffraction peak is 0.151°, and the grain size of the (003) crystal plane is The position of the (104) crystal plane diffraction peak is 44.306°, and the FWHM of the (104) crystal plane diffraction peak is 0.174°.

[0061] This embodiment also provides a method for preparing the low-cobalt positive electrode active material, comprising:

[0062] (1) The low-cobalt ternary material precursor Ni with a molar ratio of 1:1.02 0.58 Co 0.11 Mn 0.31 (OH) 2 Mixed with LiOH, sintered once in an oxygen atmosphere for 18 hours at a sintering temperature of 945° C. to obtain a first sintered product;

[0063] (2) mixing the first sintered product, titanium oxide and aluminum oxide, and performing secondary sintering for 8 hours in an oxygen atmosphere at a sintering temperature of 550° C. to obtain the low-cobalt positive electrode active material;

[0064] Among them, Ni 0.58 Co 0.11 Mn 0.31 (OH) 2 Based on the total mass of the metal elements (Li, Ni, Co, Mn, Ti and Al) in , LiOH, titanium oxide and aluminum oxide, the content of titanium element in the titanium oxide is 800ppm, and the content of aluminum element in the aluminum oxide is 1000ppm.

[0065] 1. Assembly of lithium-ion batteries

[0066] (1) Preparation of positive electrode: The low-cobalt positive electrode active material prepared in the examples of the present invention and the comparative examples, SP, CNT and PVDF were mixed with nitrogen methyl pyrrolidone (NMP) at a mass ratio of 97.5:1:0.5:1 to prepare a positive electrode slurry, and then the positive electrode slurry was coated on an aluminum foil and rolled to obtain a positive electrode;

[0067] (2) Preparation of negative electrode: Graphite, SP, CMC and SBR were mixed in a mass ratio of 95.5:1:1.5:2 to prepare a slurry, which was coated on a copper foil and rolled to obtain a negative electrode;

[0068] (3) Preparation of lithium-ion battery: The positive electrode tab made of aluminum was glued to the positive electrode, and the negative electrode tab made of copper was glued to the negative electrode. A separator with a thickness of 10 μm, an air permeability of 200 s / 100 mL, and a porosity of 40% was selected. The positive electrode, the separator, and the negative electrode were tightly stacked in order. A solute of 5 wt% LiPF was injected on both sides of the separator. 6 , an electrolyte containing EC, EMC, DMC and PC in a mass ratio of 3:4:3:0.5 as the solvent, to obtain a battery cell, and a lithium-ion battery is obtained after stacking to a required number of layers.

[0069] 2. Performance Test

[0070] (1) XRD test of low-cobalt positive electrode active materials

[0071] Half-width at half maximum (FWHM) test method: measures the peak width when the diffraction peak is half the intensity.

[0072] Grain size test method: According to the Scherrer formula, the grain size d = 0.89*γ / (B*cosθ), where γ is the X-ray wavelength, B is the half-height width of the (003) crystal plane, and θ is the diffraction angle of the (003) crystal plane.

[0073] (2) Test of stacking angle

[0074] More than 1kg of low-cobalt positive electrode active material powder is dropped from a height of 0.2m onto a plane at a speed less than 1g / s, and the powder is continuously accumulated until it is completely piled up. The acute angle between the powder accumulation slope and the plane is the accumulation angle of the powder.

[0075] (3) Testing of lithium-ion batteries:

[0076] The battery performance test system (equipment model: BTS05 / 10C8D-HP) of Shenghong Electric Co., Ltd. was used to conduct the first charge and discharge capacity test and the 800-cycle capacity retention test.

[0077] The first charge and discharge gram capacity test method: At 25°C, charge and discharge for one week at a charge and discharge rate of 0.063A / g, with a voltage range of 2.8V to 4.35V. The charge and discharge capacity obtained is divided by the amount of positive electrode used, which is the first charge / discharge gram capacity. The first discharge capacity divided by the first charge capacity is the first coulomb efficiency.

[0078] Cycle capacity retention test method: At 25°C, cycle at a charge and discharge rate of 0.19A / g (calculated based on the mass of the positive electrode material), with a voltage range of 2.8V to 4.35V. After 800 cycles, the discharge capacity of the battery at this time is divided by the discharge capacity of the first cycle, which is the 800-cycle capacity retention rate of the battery.

[0079] Examples 2 to 5 and Comparative Examples 1 to 8 are based on the steps of Example 1 with parameter changes. The specific changed parameters and test results are shown in Tables 1 to 7.

[0080] Table 1

[0081]

[0082] Table 2

[0083]

[0084] Table 3

[0085]

[0086] Table 4

[0087]

[0088] It can be seen from Table 3 and Table 4 that the titanium source and aluminum source in the present invention are sintered at appropriate contents to improve the discharge capacity, coulomb efficiency and cycle stability of the low-cobalt positive electrode active material. Comparative Example 1 and Comparative Examples 1 to 2 show that too much or too little addition of titanium element will deteriorate the cycle stability of the battery; Comparative Example 1 and Comparative Examples 3 to 4 show that too much or too little addition of aluminum element will deteriorate the cycle stability of the battery. Therefore, when the titanium source and the aluminum source are sintered at appropriate contents, they are coated on the surface of the first sintered product with better crystal plane parameters and grain parameters, which can further improve the crystallinity of the material and obtain a low-cobalt positive electrode active material with the best crystallinity and fluidity. Therefore, the discharge capacity and cycle performance of the battery in Comparative Examples 1 to 4 are lower than those in Example 1.

[0089] Table 5

[0090]

[0091] Table 6

[0092]

[0093] It can be seen from Table 5 and Table 6 that in the present invention, by controlling the temperature range of the primary sintering and the secondary sintering, and matching a specific coating material, a material with the best crystallinity and fluidity can be obtained, thereby improving the electrochemical performance of the battery. Comparative Example 1 and Comparative Examples 5 to 6 show that when the primary sintering temperature is low, the particle crystallinity is poor, the half-peak width is large, the grains are small, and the discharge gram capacity and cycle stability are both poor; when the primary sintering temperature is high, the half-peak width is small, the grains are too large, and the discharge gram capacity and cycle stability are also poor. Therefore, the first charge and discharge gram capacity, coulomb efficiency and 800-week cycle capacity retention rate of Comparative Examples 5 to 6 are all worse than those of Example 1; Comparative Example 1 and Examples 4 to 5 show that when the secondary sintering temperature is too low, the recrystallized particles are small, the discharge gram capacity and cycle stability are both poor, and when the secondary sintering temperature is too high, the recrystallized particles are large, the discharge gram capacity and cycle stability are both poor, and therefore, the comprehensive electrochemical performance of Example 1 is better than that of Examples 4 to 5.

[0094] Comparative Example 7

[0095] This comparative example is the same as Example 1 except that titanium oxide is not added in step (2).

[0096] Comparative Example 8

[0097] This comparative example is the same as Example 1 except that alumina is not added in step (2).

[0098] Table 7

[0099]

[0100] By comparing the examples in Table 7 with comparative examples 7 to 8, it can be seen that the synergistic effect of the titanium source and the aluminum source in the present invention helps the rock salt phase near the surface of the material to transform into a layered structure, thereby improving the overall crystallinity of the material. When no titanium source or aluminum source is added, the recrystallized particles are too large and the stacking angle is also too large. Therefore, the discharge gram capacity, coulomb efficiency, and cycle stability of comparative examples 7 to 8 are all worse than those of Example 1.

[0101] Based on the above embodiments 1 to 5, it can be seen that the present invention obtains a low-cobalt positive electrode active material with optimal crystallinity and fluidity by selecting a specific coating material and controlling the sintering temperature of the low-cobalt ternary material precursor and the coating material, thereby improving the charge and discharge gram capacity, coulomb efficiency and cycle capacity retention rate of the prepared electrochemical device.

[0102] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A low-cobalt positive electrode active material, characterized in that: The low-cobalt positive electrode active material comprises a low-cobalt ternary positive electrode active material core and a coating layer coated on the surface of the low-cobalt ternary positive electrode active material core, the low-cobalt ternary positive electrode active material core comprises titanium and aluminum elements, the coating layer comprises titanium compounds and aluminum compounds, and the XRD spectrum of the low-cobalt positive electrode active material satisfies: The position of the (003) crystal plane diffraction peak in the XRD spectrum is 18.40° to 18.60°, the half-height width of the (003) crystal plane diffraction peak is 0.140° to 0.160°, and the grain size of the (003) crystal plane is to The position of the (104) crystal plane diffraction peak is 44.28° to 44.32°, and the half-height width of the (104) crystal plane diffraction peak is 0.150° to 0.190°; The stacking angle of the low-cobalt positive electrode active material is 45° to 55°; The low cobalt means that in the nickel-cobalt-manganese ternary material, the amount of cobalt does not exceed 13% of the total amount of nickel-cobalt-manganese.

2. The low-cobalt positive electrode active material according to claim 1, characterized in that: Along the surface of the low-cobalt positive electrode active material inward, the distribution depth of the aluminum element in the inner core of the low-cobalt ternary positive electrode active material is higher than the distribution depth of the titanium element.

3. A method for preparing a low-cobalt positive electrode active material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing a low-cobalt ternary material precursor and a lithium salt, and sintering once at 935° C. to 955° C. to obtain a first sintered product; The amount of cobalt in the low-cobalt ternary material precursor does not exceed 13% of the total amount of the substance; (2) mixing the first sintered product, a titanium source and an aluminum source, and performing secondary sintering to obtain the low-cobalt positive electrode active material; The secondary sintering satisfies any one of the following conditions (a) and (b): (a) the secondary sintering temperature is 400° C. to 700° C.; (b) the secondary sintering time is 5h to 15h; The gas in the atmosphere of the primary sintering and the secondary sintering includes oxygen; Among them, based on the total mass of metal elements in the low-cobalt ternary material precursor, lithium salt, titanium source and aluminum source, the content of titanium element in the titanium source is 400ppm to 1200ppm, and the content of aluminum element in the aluminum source is 500ppm to 1500ppm.

4. The preparation method according to claim 3, characterized in that: The primary sintering time is 15h to 21h.

5. The preparation method according to claim 3, characterized in that: The secondary sintering temperature is 450°C to 700°C.

6. The preparation method according to claim 3, characterized in that: The volume of oxygen in the atmosphere accounts for more than or equal to 80% of the total volume of the gas.

7. The preparation method according to claim 3, characterized in that: The low-cobalt ternary material precursor, lithium salt, titanium source and aluminum source meet any one of the following conditions (c) to (f): (c) The chemical formula of the low-cobalt ternary material precursor is Ni x Co y Mn 1-x-y (OH)2, where 0.56≤x≤0.60, 0.09≤y≤0.13; (d) the lithium salt comprises lithium carbonate and / or lithium hydroxide; (e) the titanium source comprises titanium oxide; (f) The aluminum source comprises aluminum oxide.

8. An electrochemical device, characterized in that: The positive electrode of the electrochemical device comprises the low-cobalt positive electrode active material according to claim 1 or 2.

9. An electronic device, characterized in that: The electronic device comprises the electrochemical device according to claim 8.

Citation Information

Patent Citations

  • Lithium ion battery and cathode material thereof

    CN102544481A

  • Lithium ion battery positive electrode material aluminum-titanium coating preparation method

    CN103325996A